The Path of Moral Growth - Pava, Moses L. (Journal of business ethics, 2002)
This paper, following the work of the sociologist Philip Selznick, identifies three stages of moral development in organizations: ethical improvisation, ethical institutionalization, and ethical revival. I argue here that the developmental perspective is inherent in the structure of biblical narrative, especially in the stories of Genesis and Exodus. The paper concludes by debunking three common myths associated with business ethics.